Anchoring in Kepulauan Riau: Between Economic Potential and Jurisdictional Disputes - Liza Novianty; Raja Qorryna Dwi Putri Nur Asmah (Center for Maritime Policy Governance Studies (CMPGS), 2026)
This study stems from the increasing intensity of anchorage activities in the waters of the Riau Islands Province, which has dual implications: it opens up significant economic opportunities for the region, but also raises the potential for conflicts of authority between different levels of government. This situation confirms that anchorage has not only an economic dimension, but is also closely related to the issue of marine spatial management, which has yet to be fully and comprehensively managed. Therefore, this study aims to comprehensively assess the economic potential generated by anchorage activities and identify the main issues related to overlapping authorities in its management. The method used is a literature study with a descriptive approach, through research and analysis of regulations, official government reports, secondary data, and various relevant previous studies. The results of the study show that anchorage activities have the potential to be a significant source of regional income, but their utilisation has not been optimal due to policy inconsistencies, differences in regulatory interpretations, and conflicts over maritime spatial management authority. Therefore, optimising anchorage requires regulatory harmonisation, clarity in the division of authority, and strengthened intergovernmental coordination so that economic benefits can be maximised without triggering ongoing administrative conflicts